Host Adaptive Evolution of Avian-Origin H3N2 Canine Influenza Virus - Guo, Fucheng; Roy, Ayan; Wang, Ruichen; Yang, Jinjin; Zhang, Zhipeng; Luo, Wen; Shen, Xuejuan; Chen, Rui-Ai; Irwin, David M.; Shen, Yongyi (Frontiers in Microbiology, 2021)
Since its first isolation in around 2007, the avian-origin H3N2 canine influenza virus (CIV) has become established and continues to circulate in dog populations. This virus serves as a useful model for deciphering the complex evolutionary process of interspecies transmission of influenza A virus (IAV) from one species to its subsequent circulation in another mammalian host. The present investigation is a comprehensive effort to identify and characterize genetic changes that accumulated in avian-origin H3N2 CIV during its circulation in the dog. We revealed that H3N2 CIV experiences greater selection pressure with extremely high global non‐synonymous to synonymous substitution ratios per codon (dN/dS ratio) for each gene compared to the avian reservoir viruses. A total of fifty-four amino acid substitutions were observed to have accumulated and become fixed in the H3N2 CIV population based on our comprehensive codon-based frequency diagram analysis. Of these substitutions, eleven sites also display high prevalence in H3N8 CIV, indicating that convergent evolution has occurred on different lineages of CIV. Notably, six substitutions, including HA-G146S, M1-V15I, NS1-E227K, PA-C241Y, PB2-K251R and PB2-G590S, have been reported to play imperative roles in facilitating the transmission and spillover of IAVs across species barriers. Most of these substitutions were found to have become fixed in around 2015, which might have been a favorable factor that facilitating the spread of these CIV lineages from South Asia to North America and subsequent further circulation in these areas. We also detected 12 sites in 6 viral genes with evidence for positive selection by comparing the rates of non‐synonymous and synonymous substitutions at each site. Besides, our study reports trends of enhanced ongoing adaptation of H3N2 CIV to their respective host cellular systems, based on the codon adaptation index analysis, which points towards increasing fitness for efficient viral replication. In addition, a reduction in the abundance of the CpG motif, as evident from an analysis of relative dinucleotide abundance, may contribute to the successful evasion of host immune recognition. The present study provides key insights into the adaptive changes that have accumulated in the avian-origin H3N2 viral genomes during its establishment and circulation into dog populations.